Planting The Seeds of Gratitude for Sustainable Corporate Social Responsibility and The Quality of Life - Ong Cordero, Ernesto (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The study sought to determine the implementation of CSR activities and their effects on the beneficiaries' quality of life. This study used mixed-method research, combining quantitative correlational and qualitative analysis. In addition, it utilized statistical tools such as frequency, percentage, mean, weighted mean, and regression analysis. The research instrument was standardized and adopted from Kim, Uysal, and Sirgy's (2012) study entitled" How does tourism in a community impact the quality of life of community residents?" The interview used guide questions to direct the responses of the respondents. The study's subject is the 400 beneficiaries of the Southern Mindanao plantation communities. The findings revealed that the company's economic, social, cultural, and environmental CSR activities were implemented to a moderate extent. On the other hand, the beneficiaries' quality of life regarding life satisfaction under various conditions, level of life satisfaction, and satisfaction level on health and safety were categorized as reasonably satisfied. The CSR factors, such as economic, social, and cultural, were not statistically significant to claim their influence on the community's quality of life. However, though environmental factors significantly influence the community's quality of life, the extent or magnitude of its influence cannot have a significant effect as its beta coefficient is at 0.65, indicating a weak effect. Considering the findings and conclusions of the study, the following recommendations were suggested: 1. To offer more information or seminars on the preservation of the natural environment. 2. To conduct regular tree planting in the community to improve the environment and help reduce temperature, produce clean air, reduce greenhouse gasses, and prevent flooding and soil erosion. 3. To teach the community proper waste disposal at home through Green Alternatives, the Five R's Reduce, Reuse, Repair, Rot, and Recycle. 4. To determine program services that will change and expand the community/students' needs. 5. To conduct a workshop on CSR's goals and objectives to increase the level of awareness of the beneficiaries on the accurate picture of CSR in their lives, 6. For the companies/administrators to apply the proposed strategic approaches in enhancing the CSR programs to their beneficiaries.